Nuclear forms of superoxide dismutase, catalase and peroxidase - Protas, A. F. (Биополимеры и клетка, 1996)
Nuclei of rat brain cortex cells contain ownspecific forms of superoxide dismutase (SOD), catalase (CAT) and gluthatione peroxidase (GPx). The enzymes are firmly associated with chromatin, preferationally with transcriptionally active fraction and released from nuclei completely with >1.2 M Nad. Mr of SOD is 10 kDa, CAT and GP× 44 kDa (gel-filtration). Isoelectric points of SOD is under pH 6.0, CAT and GPx 5.8 ( chromatofocusing). The activities of enzymes depend on ionic strength and are maximal under >1.1 MNaCl. Nuclear SOD are not inhibited with KCNand thus, it is MnSOD.